Distribution of Estimated 10-Year Risk of Recurrent Vascular Events and Residual Risk in a Secondary Prevention Population. Issue 19 (8th November 2016) - Kaasenbrood, Lotte; Boekholdt, S. Matthijs; van der Graaf, Yolanda; Ray, Kausik K.; Peters, Ron J.G.; Kastelein, John J.P.; Amarenco, Pierre; LaRosa, John C.; Cramer, Maarten J.M.; Westerink, Jan; Kappelle, L. Jaap; de Borst, Gert J.; et al.
Abstract : Background: Among patients with clinically manifest vascular disease, the risk of recurrent vascular events is likely to vary. We assessed the distribution of estimated 10-year risk of recurrent vascular events in a secondary prevention population. We also estimated the potential risk reduction and residual risk that can be achieved if patients reach guideline-recommended risk factor targets. Methods: The SMART score (Second Manifestations of Arterial Disease) for 10-year risk of myocardial infarction, stroke, or vascular death was applied to 6904 patients with vascular disease. The risk score was externally validated in 18 436 patients with various manifestations of vascular disease from the TNT (Treating to New Targets), IDEAL (Incremental Decrease in End Points Through Aggressive Lipid Lowering), SPARCL (Stroke Prevention by Aggressive Reduction in Cholesterol Levels), and CAPRIE (Clopidogrel Versus Aspirin in Patients at Risk of Ischemic Events) trials. The residual risk at guideline-recommended targets was estimated by applying relative risk reductions from meta-analyses to the estimated risk for targets for systolic blood pressure, low-density lipoprotein cholesterol, smoking, physical activity, and use of antithrombotic agents. Results: The external performance of the SMART risk score was reasonable, apart from overestimation of risk in patients with 10-year risk >40%. In patients with various manifestations of vascular disease, median 10-year risk of a recurrent major vascular event was 17% (interquartile range, 11%–28%), varying from <10% in 18% to >30% in 22% of the patients. If risk factors were at guideline-recommended targets, the residual 10-year risk would be <10% in 47% and >30% in 9% of the patients (median, 11%; interquartile range, 7%–17%). Conclusions: Among patients with vascular disease, there is very substantial variation in estimated 10-year risk of recurrent vascular events. If all modifiable risk factors were at guideline-recommended targets, half of the patients would have a 10-year risk <10%. These data suggest that even with optimal treatment, many patients with vascular disease will remain at >20% and even >30% 10-year risk, clearly delineating an area of substantial unmet medical need. Abstract : Supplemental Digital Content is available in the text.